Military Occupational Outcomes in Canadian Armed Forces Personnel with and without Deployment-Related Mental Disorders. (June 2016) - Boulos, David; Zamorski, Mark A.
Objective: Mental disorders are common in military organizations, and these frequently lead to functional impairments that can interfere with duties and lead to costly attrition. In Canada, the military mental health system has received heavy investment to improve occupational outcomes. We investigated military occupational outcomes of diagnosed mental disorders in a cohort of 30, 513 personnel who deployed on the Afghanistan mission. Methods: Cohort members were military personnel who deployed on the Afghanistan mission from 2001 to 2008. Mental disorder diagnoses and their attribution to the Afghanistan mission were ascertained via medical records in a stratified random sample ( n = 2014). Career-limiting medical conditions (that is, condition-associated restrictions that reliably lead to medically related attrition) were determined using administrative data. Outcomes were assessed from first Afghanistan-related deployment return. Results: At 5 years of follow-up, the Kaplan-Meier estimated cumulative fraction with career-limiting medical conditions was 40.9% (95% confidence interval [CI] 35.5 to 46.4) among individuals with Afghanistan service–related mental disorders (ARMD), 23.6% (CI 15.5 to 31.8) with other mental disorders, and 11.1% (CI 8.9 to 13.3) without mental disorders. The adjusted Cox regression hazard ratios for career-limiting medical condition risk were 4.89 (CI 3.85 to 6.23) among individuals with ARMD and 2.31 (CI 1.48 to 3.60) with other mental disorders, relative to those without mental disorders. Conclusions: Notwithstanding the Canadian military's mental health system investments, mental disorders (particularly ARMD) still led to a high risk of adverse military occupational outcomes. Such investments have intrinsic value but may not translate into reduced medically related attrition without improvements in prevention and treatment effectiveness.